Analyzing the Mathematical Models behind the Collective Intelligence of Bees - B, Selva Rani; S, Vairamuthu (IJRDO -Journal of Computer Science Engineering, 2015)
For any system, a mathematical model is a generalization and representation of its features in a veryprecise manner.In this paper, we carried out a survey on mathematical models behind the bees. The term collectiveintelligence, popularly known as swarm intelligence studies the cooperative behavior among the naturalspecies. This self-organized; de-centralized intelligence and cooperation among individuals of a group likeants, bacteria, bees, birds, fishes, termites, wolves, pelicans etc. help them to achieve a common goal likeforaging, defending, constructing nests and so on. They frame and follow very simple rules in their entirelife cycle, communicate locally in an efficient manner, assist each other in all the situations and manyscientific and engineering problems have been solved inspired by these characteristics of swarms.